Language learning policies and opportunities for migrants and their practical implementation in Austria - Eva Konrad; Viktoria Ebner; Benjamin Kremmel (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2024)
This paper aims to provide an overview of current language policies in Austria. It examines the legal frameworks and current practices concerning migration, drawing on the historical development of and the current political discourse in Austria. The principal objective of the paper is to describe how language policies are operationalized through the implementation of language requirements, learning opportunities and language tests for migrants.